Application of the Forward Chaining Method in Building a Student Counseling Expert System at SMAN 03 Bengkulu City - Adriansyah, David; Asnawati, Asnawati; Suryana , Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
Implementation of guidance and counseling in schools has a very important role in realizing students as individuals who are independent, responsible, creative and productive workers. Guidance and counseling for students is needed in making appropriate choices or to solve problems faced by students. The student counseling expert system at SMA Negeri 3 Bengkulu City was created to facilitate the counseling process for students in schools based on the problems and symptoms experienced by students. This expert system adopts the knowledge of the BK teacher, where there are 25 problems that often occur in schools. In the process of diagnosing the results of student consultations, the application will select the problems experienced by students, then choose the symptoms experienced by students, thus displaying the possible percentage level of the problem. The student counseling expert system at SMA Negeri 3 Bengkulu City was created using the Visual Basic .Net programming language. Based on the tests that have been carried out, the functionality of the student counseling expert system at SMA Negeri 3 Bengkulu City runs as expected, and the application is able to display the results of student counseling consultations through the possible percentage levels of problems and symptoms experienced by students.